2017
DOI: 10.1038/s41598-017-14609-0
|View full text |Cite
|
Sign up to set email alerts
|

Transition of colistin dependence into colistin resistance in Acinetobacter baumannii

Abstract: We recently demonstrated a high rate of colistin dependence in Acinetobacter baumannii isolates exposed to colistin in vitro. In the present study, we obtained a colistin-resistant (H08-391R) and colistin-dependent mutant (H08-391D) from a colistin-susceptible parental strain (H08-391). We found that the colistin-dependent mutant converted into a stable colistin-resistant mutant (H08-391D-R) in vitro after four serial passages without colistin. H08-391D and H08-391D-R were both found to harbor defective lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 25 publications
4
39
0
1
Order By: Relevance
“…Although rare, cases where bacteria have developed a dependence on an antibacterial compound for growth have been described, for example with streptomycin, colistin, and vancomycin ( 8 , 50 – 55 ). Here we describe the isolation of K. pneumoniae mutants whose growth requires the inhibition of LpxC.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, cases where bacteria have developed a dependence on an antibacterial compound for growth have been described, for example with streptomycin, colistin, and vancomycin ( 8 , 50 – 55 ). Here we describe the isolation of K. pneumoniae mutants whose growth requires the inhibition of LpxC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the development of colistin-dependent mutants may have clinical significance, and it should be investigated. A recent study showed that the colistin-dependent phenotype may arise from the loss of LPS or defects in its structure, resulting from the disruption of LpxC [83]. In that study, transition of colistin dependence into colistin resistance was also demonstrated in the absence of antibiotic selection pressure [83].…”
Section: ~10mentioning
confidence: 91%
“…However, resistance towards colistin among A. baumannii has become a serious problem as there are no alternative available therapeutic options. 6 There are now reports from different regions of the world of pan-drug-resistant (PDR) A. baumannii. 7 The primary resistance mechanism is mediated through the modification of the lipid A moiety of lipopolysaccharide (LPS) through the addition of phosphoethanolamine (PEtN) through overexpression and/or mutations in the two-component regulatory system PmrA and PmrB.…”
Section: Introductionmentioning
confidence: 99%